HUBUNGAN PENGETAHUAN PENDERITA HIPERTENSI TENTANG STROKE DENGAN PERILAKU PENCEGAHAN STROKE DI PUSKESMAS HELVETIA MEDAN TAHUN 2016 - Hamonangan Damanik (Universitas Prima Indonesia, 2018)
The quality of working life is one way to improve the performance of nurses as it will contribute to the success of the organization and the positive impact for the organization. The aim of this study was to determine the relationship of the quality of working life with the performance of nurses in a private hospital in Medan in 2015. This study is a quantitative research with cross sectional design. The population in this study are all nurses there diruang inpatient Imelda Hospital as many as 134 people. The amount of sample is 57 people, the type of sampling using simple random sampling method. Analysis of data using univariate analysis, bivariate analysis with Pearson Correlation test to analyze the relationship between the quality of working life with the performance of nurses at Imelda Hospital Medan. The findings of the data analysis with Pearson Correlation test obtained by value p> 0.05 (p = 0.452), which means there is no significant relationship between the quality of working life with nurse performance, and quality of work life factors that have a significant relationship with performance is a factor compensation A balanced, problem solving and the factors factor pride for the institution, while other factors have no significant relationship with performance. Recommended to the hospital management to continue to improve the application of the quality of work life of nurses by performing career development, job coaching nurses, monitor and evaluate on an ongoing basis so that the performance of nurses continues to be improved.